Old cemeteries as refuge of the steppe flora in Southern Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2021)
Changes in natural landscapes and economic activities lead to the loss of a large proportion of the steppes. Recent studies (2008–2017) have demonstrated the high importance of old cemeteries, that contribute to the preservation of steppe red-listed steppe species. The area of the old cemeteries of the Lower Dnieper varies from 0.43 ha to 6.79 ha. The list of vascular plants from 10 cemeteries of the Lower Dnieper region includes 388 species belonging to 226 genera, 62 families, 3 classes and 2 divisions. The total number of species within cemetery varied from 104 to 217 (on average 153 species). In old cemeteries of the studied region, rare steppe species have survived, although steppe vegetation is preserved where there are fragments of virgin and unploughed steppes around the cemeteries, near old villages or cities. 22 protected vascular plant species were found in the studied old cemeteries (5.65 % of the total species pool). Five of these are included in the Red Data Book of Ukraine: Astragalus henningii, Stipa capillata, Stipa lessingiana, Stipa ucrainica, Tulipa biebersteiniana. 17 species of vascular plants are included in the Red List of the Kherson region: Amygdalus nana, Bellevalia sarmatica, Centaurea trichocephalla, Convallaria majalis, Dianthus andrzejowskianus, Elytrigia pseudocaesia, Ephedra distachya, Fraxinus excelsior, Iris halophila, Limonium platyphyllum, Linaria macroura, Muscari neglectum, Peucedanum ruthenicum, Prangos odontalgica, Quercus robur, Veronica capsellicarpa, Vinca herbacea.
Keywords: Lower Dnieper, steppe, cultural heritage sites, vascular plants, flora, sozophytes, in situ.